Expression for the electrical efficiency of photovoltaic modules in different photovoltaic thermal (PVT) configurations. (2021) - Mishra, R.K.; Tripathi, Rajesh; Gupta, V.S.; Dwivedi, V.K.
Highlights: Thermal modeling for semitransparent and opaque PV module. Effect of water flow over the top surface of PV module. Temperature dependent electrical efficiency of photovoltaic thermal (PVT) modules. Abstract: In present communication, analytical expressions have been developed for electrical efficiency of an opaque (G-T) and a semitransparent (G-G) Photovoltaic panels in different photovoltaic thermal (PVT) configurations. Water and air are used for withdrawing the heat linked with the solar panel. Four configurations of opaque and semitransparent type PV modules have been discussed here. Namely case I: opaque solar panel where water flows above the module; case II: semitransparent solar panel where water flows above the panel; case III: opaque solar panel where air flows at beneath of the panel through duct and water flows above the panel and case IV: semitransparent solar panel where air flows at beneath of the panel through duct and water flows above the panel have been considered for the present study. It has been observed that case IV gives better results with related to the electrical energy generation among all four cases. Average electrical efficiency is increased by 2.29% and 4.17% respectively from case I to III and from case II–IV.